A Rh(iii)-catalyzed regioselective intermolecular oxa-Pauson–Khand reaction of alkynes, arylboronic acids and CO to form butenolides. Issue 5 (10th February 2020) - Zhao, Mi-Na; Zhang, Ying; Ge, Ning; Yu, Le; Wang, Shun; Ren, Zhi-Hui; Guan, Zheng-Hui
Abstract : A Rh(iii )-catalyzed regioselective intermolecular oxa-Pauson–Khand reaction of arylboronic acids, alkynes and CO for the synthesis of butenolides has been developed. Abstract : A Rh(iii )-catalyzed regioselective intermolecular oxa-Pauson–Khand reaction of arylboronic acids, alkynes and CO for the synthesis of butenolides has been developed. The multi-step reaction proceeded smoothly in the presence of [RhCp*Cl2 ]2 catalyst, NaOAc base and CH3 OH additive. The reaction used readily available starting materials, tolerated various functional groups, and afforded valuable butenolides in good yields with high regioselectivity.